The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fpsyg.2023.1127194
|View full text |Cite
|
Sign up to set email alerts
|

Social support and prosocial behavior in Chinese college students during the COVID-19 outbreak: a moderated mediation model of positive affect and parental care

Abstract: PurposeProsocial behavior (PSB) plays a critical role in everyday society, especially during the pandemic of COVID-19. Understanding the underlying mechanism will provide insight and advance its implementation. According to the theory of PSB, social interaction, family and individual characters all contribute to its development. The current study aimed to investigate the influencing factor of PSB among Chinese college students during COVID-19 outbreak. This is an attempt to understand the mechanism of PSB and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 93 publications
1
4
0
Order By: Relevance
“…The result is consistent with the COR theory (Hobfoll, 1989), which states that in the face of stressful situations, individuals with positive affectivity traits tend to be more confident and committed to their work through the availability of social support within their organization. The results also supported previous studies, which state that employees who exhibit positive affectivity traits are more likely to develop healthy social relationships at their workplace, leading to increased social support within the organization (Çivitci, 2015;Diener et al, 2020;Huang et al, 2023). The result implies that employees may be friendly, active, sociable and assertive, but this does not stop them from seeking support from their supervisor to remain active at work.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The result is consistent with the COR theory (Hobfoll, 1989), which states that in the face of stressful situations, individuals with positive affectivity traits tend to be more confident and committed to their work through the availability of social support within their organization. The results also supported previous studies, which state that employees who exhibit positive affectivity traits are more likely to develop healthy social relationships at their workplace, leading to increased social support within the organization (Çivitci, 2015;Diener et al, 2020;Huang et al, 2023). The result implies that employees may be friendly, active, sociable and assertive, but this does not stop them from seeking support from their supervisor to remain active at work.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, individuals with positive affectivity always strive to create a positive working environment for others to be happy with their work (Hui et al, 2007). As a result, obtaining support and cooperation from both the organization and team members will give them the enthusiasm to influence and improve the mood of others around them (Huang et al, 2023). According to Çivitci (2015), employees will increase positive affectivity and lower negative affectivity when they obtain social support from co-workers or supervisors because substantial support from a co-worker or supervisor will make them gain more self-esteem and confidence to relate with others.…”
Section: Positive Affectivity and Social Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Its broad utilization spans across multiple scientific and research disciplines, encompassing fields such as social sciences, informatics and psychology (e.g. Credamo, 2023; Huang et al ., 2023). Moreover, Credamo incorporates an examination of various factors, including survey completion time and participant attentiveness, to effectively manage and ensure the quality of responses (Credamo, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Hellmann et al [28] demonstrated that the endorsement of prosocial values among German people increased at the beginning of the COVID-19 pandemic. There is also some evidence [29][30][31][32][33][34] of a link between prosocial behavior and psychological well-being during the COVID-19 pandemic. The literature indicates that positive emotions increase one's proclivity towards prosocial behavior [35, 36; for a review, see : 37].…”
Section: Pretraumatic Stress and Prosocial Behaviormentioning
confidence: 99%